Un prototype SIG pour analyser la résilience urbaine : application à la ville de Dublin - Serge Lhomme; Richard Laganier; Youssef Diab; Damien Serre (VertigO)
Resilience is a buzzword which highlights numerous debates in academic field, particularly concerning its practical relevance. That is why researches concerning methodologies development and tools in order to analyze resilience are particularly important. Thus this research proposes a methodology for analyzing urban resilience and introduces the development of a prototype to operationalize this methodology. The methodology is focused on a preliminary urban networks resilience analysis and is implemented using a Web-GIS prototype. Then methodology and prototype are used for analyzing resilience of Dublin city. Complex relationships identification between risks and territories, highlighted by this research, seems demonstrate practical relevance of resilience concept.